The Melanesian Spearhead Group in terms of Indonesia’s interest - Zahidi – MA, M. Syaprin (Przegląd Politologiczny, 2018)
This qualitative study aims to encompass Indonesia’s interest in seeking to join the MSG (Melanesian Spearhead Group). An in-depth interview was carried out with the Director of Directorate General of Asia, Pacific, and Africa under the Ministry of Foreign Affairs of the Republic of Indonesia aiming to obtain valid data supported by literature reviews. The findings indicate that Indonesia’s attempts to join the MSG or Melanesian intergovernmental organizations basically aim to maintain domestic stability which, in this context, refers to closing down separatist movements that still exist in Indonesia, such as the FPM (Free Papua Movement), that explicitly receive international support from Melanesian countries sharing the same racial background. In an effort to preserve the country’s sovereignty, Indonesia, in the era of President Joko Widodo, strives to join the MSG to prevent the Melanesian intergovernmental organization from supporting such separatist groups, which from Indonesia’s perspective could disrupt the unity of the Republic of Indonesia.